Aplikasi E-Commerce pada YHEL-VIE Computer - WIDYASTUTI, RINI (Jurnal EDik Informatika, 2019)
With e-commerce companies can establish business relationships with business partners or their cuctomers more efficiently, it is because of all the components involved in business processes such as customer service, product or service available, promotion and payment method applied by e-commerce. This encourages the development of internet entrepreneurs to market their products on the internet, as well as Computer Yhel-vie engaged in the sale of computer equipment, the development of product that they have, the more also problems to be addressed, such as stock management, product management, report generation and the slow process of the transaction. Computer Yhel-vie is still limited in terms of promotion are still relying on consumer-to-consumer promotion through other close relatives or distributor.Keyword : E-commerce, internet entrepreneurs.